Generating Ionic Liquids from Ionic Solids: An Investigation of the Melting Behavior of Binary Mixtures of Ionic Liquids - Maximo, Guilherme J.
Mixtures of ionic liquids (ILs) allow enlarging the plethora of the physical and chemical properties of these materials in addition to the well-known tunable character associated with pure compounds. It is shown here that mixtures also induce a significant decrease of the melting points of the mixture to values well below those of the original compounds allowing the tuning of the melting point of an ionic liquid mixture and the generation of novel ionic liquids from mesotherm salts. This work evaluates the melting behavior of mixtures of seven hexafluorophosphate-based compounds combined with imidazolium-, pyridinium-, pyrrolidinium-, piperidinium- ammonium-, or phosphonium-based cations. The solid-liquid equilibrium phase diagrams of nine of their binary mixtures were measured using optical microscopy and differential scanning calorimetry. The pure ILs' melting profile reveals the presence of polymorphs with highly energetic solid-solid transitions that are relevant for the evaluation of these systems. The phase diagrams reported here also allow an investigation on the nonideality of the mixtures of ionic liquids. A classical thermodynamic approach shows that while most of the mixtures investigated present an ideal liquid behavior, others show slight or even marked nonideal profiles. One particular system, [C(3)mpyr][PF6] (1-methyl-1-propylpyrrolidinium hexafluorophosphate) + [C(3)mpip][PF6] (1-methyl-1-propylpiperidinium hexafluorophosphate), displays a continuous solid solution as established by differential scanning calorimetry, powder X-ray diffraction, and crystallographic data being one of the few ionic liquid alloys ever reported.